2018
DOI: 10.1021/acs.macromol.8b01795
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Form II to I Transition in Low Molar Mass Polybutene-1 at Crystallization Temperature Reveals Stabilization Role of Intercrystalline Links and Entanglements for Metastable Form II Crystals

Abstract: As for the solid−solid transformation from form II to form I in polybutene-1, the intercrystalline links in amorphous phase and the temperature difference between crystallization and phase transition were thought to be essential in previous studies for generating the internal stress to promote nucleation and growth of the phase transition. In this work, we report experimental evidence showing that such a transition can be accomplished without supercooling at the temperature of crystallization directly in a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 56 publications
5
81
0
Order By: Relevance
“…In the early stage, it promotes form I nucleation; however, it becomes a retardance factor in the later stage. It is not as claimed either by classical view that the intercrystalline links always promoted form I nucleation or by recent view that the intercrystalline links only stabilize the metastable form II …”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the early stage, it promotes form I nucleation; however, it becomes a retardance factor in the later stage. It is not as claimed either by classical view that the intercrystalline links always promoted form I nucleation or by recent view that the intercrystalline links only stabilize the metastable form II …”
Section: Discussionmentioning
confidence: 94%
“…Owing to special long chain conformation, polymer often forms different crystalline structure under different crystalline condition, and kinetically favored phases will transform to thermodynamically stable phase, for example, orthorhombic‐to‐hexagonal phase transition of polyethylene, mesomorphic‐to‐monoclinic phase transition of isotactic polypropylene, form II‐to‐form I phase transition of polybutene‐1 (PB‐1), disorder‐to‐order phase transition of poly( l ‐lactide), β‐to‐α phase transition of poly(butylene adipate), and so on. Among these phase transitions, form II‐to‐form I phase transition is an important kind of phase transition, receiving considerable attention in recent years . An important reason is that the production of PB‐1 was increased greatly in the past decades; however, the constraint of the phase transition on the melt processing has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular structure can be designed by varying molecular weight, as well as regularity, or incorporating the extra structural co-units. Recently, Qiao et al studied the correlation of the II-I phase transition with molecular weights in a polybutene-1 homopolymer [12,33,34]. It was found that high molecular weight facilitates the formation of the intercrystallite links because of the relative large radius of gyration, with respect to the stacking size of crystalline and amorphous domains, which enhances stress transfer into the lamellae.…”
Section: Introductionmentioning
confidence: 99%